One new genus and six new species of the subfamily Asopinae (Pentatomida: Heteroptera) for Vietnam - Khuong, Dang Duc (Academia Journal of Biology, 2014)
One new genus and six new species of the subfamily Asopinae (Pentatomida: Heteroptera) for Vietnam